ECOLOGICAL CHARACTERISTICS OF POLICE INSECTS AND THEIR DAMAGE TO AGRICULTURE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Abstract: The article describes the characteristics and degree of harmfulness of lepidopteran insect pests, their impact on the quality and volume of crop yields and their economic consequences. Based on the conducted research, it was established that of all 158 species of lepidopteran insects, 34 species (21.5%) are the main pest species. The degree of harmfulness of these species is explained at the level of 3 groups. In particular, 21 of the dominant species (61.8%) are particularly dangerous facultative pests that cause serious damage when favorable conditions arise. 9 (26.5%) species are dangerous pests that cause serious damage, and 4 (11.8%) species are among the extremely dangerous pests included in the quarantine list. Also, the features and degree of harmfulness of the main species are highlighted.